Damage of plasma-facing materials exposed to powerful plasma streams in ITER-relevant conditions - Makhlai, V. A.; Aksenov, N. N.; Byrka, O. V.; Garkusha, I. E.; Herashchenko, S. S.; Malykhin, S. V. (Київський національний університет ім. Тараса Шевченка, 2016)
The damage of tungsten (W) which is chosen as main plasma facing material relevant to International Thermonuclear Experimental Reactor (ITER) have been studied in experimental simulations of ITER-like transient events with quasi-stationary plasma accelerator QSPA Kh-50. Heat loads to exposed surfaces achieved 1 MJ/m2 (the pulse duration of 0.25 ms). The large and fine cracks appeared in result of plasma impacts. Heat loads accompanied by pronounced melting of tungsten cause an intense ejection of liquid droplets and solid dust. Re-deposition of the eroded material is observed also. The most important erosion mechanism connected with the edge effects in 3D geometry of targets has been studied. Such mechanism results in an increase in the size of the emitted droplets as compared with those emitted from a flat surface.